Polycythemia Mimicking Venous Sinus Thrombosis - Healy, John F. (AJNR Am J Neuroradiol, 2002)
Summary: Venous sinus thrombosis is a relatively uncommon disorder that frequently is associated with confusing clinical findings and delayed diagnosis. Patients are often screened with unenhanced CT, and CT findings may be subtle and may include hyperattenuation of cerebral veins or venous sinuses secondary to intracranial thrombosis. This hyperattenuation may be mimicked by polycythemia, as shown in this case.